2011
DOI: 10.1016/j.atherosclerosis.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ezetimibe on peripheral arterial atherosclerosis depends upon statin use at baseline

Abstract: Background Both statins and ezetimibe lower LDL-C, but ezetimibe’s effect on atherosclerosis is controversial. We hypothesized that lowering LDL-C cholesterol by adding ezetimibe to statin therapy would regress atherosclerosis measured by magnetic resonance imaging (MRI) in the superficial femoral artery (SFA) in peripheral arterial disease (PAD). Methods – Atherosclerotic plaque volume was measured in the proximal 15–20 cm of the SFA in 67 PAD patients (age 63±10, ABI 0.69±0.14) at baseline and annually x 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 26 publications
1
58
0
Order By: Relevance
“…Even after release of the ENHANCE trial, and several other clinical trials that have failed to demonstrate a beneficial effect of ezetimibe on clinical outcomes, 1416 ezetimibe continues to be initiated as new therapy, both as monotherapy and as therapy concomitant with other lipid-lowering agents. And, in contrast to professional guidelines and expert recommendations that broadly reinforce first use of statins along with exercise and dietary modification to prevent cardiovascular disease, 17,20–22 more than half of adults who newly initiate ezetimibe do so without prior use of another lipid-lowering agent, statins in particular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after release of the ENHANCE trial, and several other clinical trials that have failed to demonstrate a beneficial effect of ezetimibe on clinical outcomes, 1416 ezetimibe continues to be initiated as new therapy, both as monotherapy and as therapy concomitant with other lipid-lowering agents. And, in contrast to professional guidelines and expert recommendations that broadly reinforce first use of statins along with exercise and dietary modification to prevent cardiovascular disease, 17,20–22 more than half of adults who newly initiate ezetimibe do so without prior use of another lipid-lowering agent, statins in particular.…”
Section: Discussionmentioning
confidence: 99%
“…In the ensuing years, ezetimibe sales rebounded and now again exceed a billion dollars per year, 12,13 as several additional clinical trials have been published that similarly showed that the drug lowered LDL cholesterol levels, although all failed to demonstrate a beneficial effect of ezetimibe on clinical outcomes. 1416 …”
Section: Introductionmentioning
confidence: 99%
“…29 In patients who received statin pretreatment, atorvastatin/ezetimibe combination had greater effect in reducing %PV compared with atorvastatin alone (−1.8% vs. −0.1%, P=0.002), whereas a non-significant effect was observed in patients who did not receive statin pretreatment (−1.3 vs. −0.9, P=0.12). In addition, West et al found that statin-naïve patients randomized to statin plus ezetimibe or statin alone had similar changes in peripheral PV despite a significant reduction in LDL-C. 30 Furthermore, in the placebo arm of the Global Assessment of Plaque Regression With a PCSK9 Antibody as Measured by Intravascular Ultrasound (GLAGOV) trial, 98.3% of patients had statin pre-treatment, and baseline mean LDL-C was 92.4 mg/dL. 31 Neither %PV nor total PV changed from baseline to 78-week follow-up, indicating that the effect of statin on PV is not long-lasting.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque calcification assessed by CT is associated with increased risk of amputations in PAD patients. 61 The adverse effects of particular features related to plaque composition in coronary and carotid arteries have been well studied and include high risk plaque characteristics such as intra-plaque hemorrhage (IPH), lipid rich necrotic core (LRNC), or thinned fibrous caps. 6264 The clinical impact of these characteristics in the peripheral arteries is still being studied.…”
Section: Mri Assessment Of Peripheral Arterial Plaquementioning
confidence: 99%